Pelatihan Berkelanjutan Pengelolaan Limbah Sampah Dusun Klithak, Ngluwar, Kabupaten Magelang - Adhivinna, Vidya Vitta; Diansari, Rani Eka; Adyaksana, Rahandhika Ivan; ennisa; Purnama, Hari (DHARMA BAKTI, 2021)
Community service was held in Klitak Sub-Village, Pakunden Village, Ngluwar District, Magelang Regency. This devotional activity is in the form of coaching, counseling, and mentoring in the processing of household waste in order to help reduce environmental pollution. In addition, it can also produce a product from waste that can increase people's income. The purpose of this community service program is to educate the community about waste management, this activity is an ongoing activity of the community service program that has been implemented before. This activity is expected to complete the previous activities that only focus on sorting waste alone have not been focused primarily on waste management. This service activity is carried out with a duration of approximately 2 hours each arrival according to the scheduled time and agreed together with the villagers and village officials.